CHRNB1‐associated congenital myasthenia syndrome: Expanding the clinical spectrum. Issue 3 (9th December 2020) - Freed, Amanda S.; Schwarz, Anisha C.; Brei, Brianna K.; Clowes Candadai, Sarah V.; Thies, Jenny; Mah, Jean K.; Chabra, Shilpi; Wang, Leo; Innes, A. Micheil; Bennett, James T.
Abstract: CHRNB1 encodes the β subunit of the acetylcholine receptor (AChR) at the neuromuscular junction. Inherited defects in the neuromuscular junction can lead to congenital myasthenia syndrome (CMS), a clinically and genetically heterogeneous group of disorders which includes fetal akinesia deformation sequence (FADS) on the severe end of the spectrum. Here, we report two unrelated families with biallelic CHRNB1 variants, and in each family, one child presented with lethal FADS. We contrast the diagnostic odysseys in the two families, one of which lasted 16 years while the other, utilizing rapid exome sequencing, led to specific treatment in the first 2 weeks of life. Furthermore, we note that CHRNB1 variants may be under‐recognized because in both families, one of the variants is a single exon deletion that has been previously described but may not easily be detected in clinically available genetic testing.